RANCANG BANGUN SISTEM INFORMASI PEMESANAN MENU MAKANAN PADA KATERING KUSUMA JAYA BERBASIS WEB : RANCANG BANGUN SISTEM INFORMASI PEMESANAN MENU MAKANAN PADA KATERING KUSUMA JAYA BERBASIS WEB - Pribadi, Rebicha Juwita Setyaning; Karyanto, Nonot Wisnu (Melek IT : Information Technology Journal, 2022)
Kusuma jaya catering is an industry engaged in the food sector in collaboration with PT. Asahimas Flat Glass Tbk, made food deliveries every day on that day, Kusuma jaya officers still did how to order manually, to place orders, and also recording which was still done manually which was considered inefficient, so that's where the formation of the food menu ordering system This is aimed at assisting the caterer in seeing orders, and can also help buyers if they want to order in large quantities, so that incoming orders are recorded in the system, an information system that will be designed to help Kusuma Jaya Catering to manage how much food is ordered. The system to be used is web-based using the PHP programming language, MySQL. The methodology used is waterfaal building design. So the design of the food menu ordering information system at the Kusuma Jaya catering is based on the display of research results that can make it easier for customers to order food menus. Then the results that will be obtained by the catering party can find out the incoming orders and how much. In conclusion, with this system the catering party can find out the number of incoming orders, and buyers can view order data and can also order food menus in large quantities.